Comparative Study of Antioxidant and Cytotoxic Activities of Abrus precatorius Extracts from the Biofarmaka Herbal Garden and the Materia Medica Garden Batu - Christy, Chika Lovenia; Rani Wardani Hakim (Writing Center IMERI FMUI, 2025)
Breast cancer remains the leading cause of cancer incidence and mortality among women. Doxorubicin is a mainstay in breast cancer therapy; however, its use is limited by toxicity and adverse effects. Abrus precatorius (APC) contains bioactive compounds with antioxidant and anticancer potential, though variations in growing conditions may influence its activity. This study compared the antioxidant and cytotoxic activities of 70% ethanol leaf extracts of APC from the Biofarmaka Garden (Bogor, West Java) and the Materia Medica Garden (Batu, East Java). Qualitative phytochemical screening was performed to identify secondary metabolites. Antioxidant activity was evaluated using the DPPH assay with vitamin C as the positive control, while cytotoxic activity was assessed against MCF-7 cells using the MTT assay with doxorubicin as the positive control. IC₅₀ values were calculated and analyzed using independent t-test and Mann–Whitney test. Both extracts contained saponins, flavonoids, tannins, alkaloids, and steroids. Antioxidant activity was moderate with IC₅₀ values of 175.70 ± 0.69 µg/mL (Bogor) and 173.07 ± 0.07 µg/mL (Batu) (p = 0.021). Cytotoxic activity was weak with IC₅₀ values of 264.51 ± 8.11 µg/mL (Bogor) and 257.35 ± 33.92 µg/mL (Batu) (p = 0.513). Both extracts showed similar phytochemical profiles, with moderate antioxidant and weak cytotoxic activities against MCF-7 cells. Keywords: Abrus precatorius, antioxidant, cytotoxic, MCF-7, IC50